Oscillation of second-order strongly superlinear and strongly sublinear dynamic equations - Grace, Said R.; Agarwal, Ravi P.; Bohner, Martin; O’Regan, Donal (Communications in nonlinear science & numerical simulation, 2009)
We establish some new criteria for the oscillation of second-order nonlinear dynamic equations on a time scale. We study the case of strongly superlinear and the case of strongly sublinear equations subject to various conditions.